EVALUASI ANTARMUKA WEBSITE SMKN DI TANJUNGPANDAN BELITUNG MENGGUNAKAN USABILITY TESTING - Brama Wahyu Prabowo; Bambang Soedijono; Sudarmawan Sudarmawan (Universitas Janabadra, 2020)
Information system plays an important role in a company or educational institution, especially SMKN in Tanjungpandan Belitung in order to promote, administer, display competitive advantages for each study program owned by the State Vocational High School in Tanjungpandan Belitung via its website. Government institutions such as schools should have a website and think of new innovations in order to compete and survive in the fierce business education competition. As one of the information services, it is necessary to build a website that handles requests from many users well.Website has an interface or interface that serves to interact between users with the technology itself. Information technology with one another has a different interface design according to the functions and needs of users. Making the user interface which aims to make information technology easier to use by users or unfamiliar is called user friendly.Research to be conducted by researchers has differences in data retrieval because this test will use the Usability and Golden Rules method of using Usability Testing is used to evaluate and modify website performance while the Golden Rules are used to evaluate the website design from the measurement of the two methods bringing up a new measurement tool. The results of the study can be used as input for website development at the Vocational Middle School in Tanjungpandan Belitung. Keywords: Website – SMKN – Usability – Golden Rules